Analisis Faktor yang Mempengaruhi Etos Kerja Penyuluh Agama Kristen - Tiur Imeldawati; Hermanda Ihut Tua Simamora; Dame Taruli; Elsina Sihombing; Winda Manalu (Sekolah Tinggi Teologi Intheos Surakarta, 2024)
Abstract. Christian Religion Extension Workers face great challenges in carrying out their duties, so they require a high work ethics to maximize their performance. The aim of this research was to analyze various factors that influence the performance of Christian Religion Extension Workers. Through quantitative research, an analysis of factors was carried out that had a significant influence on the work ethics of Christian Religion Extension Workers at the Ministry of Religion, Toba Regency. The research result showed that among the career development system factor, salary factor, work environment factor, social factor, competency factor and appreciation factor, the career development system factor is the most dominant in increasing the work ethics of Christian Religion Extension Workers. Thus, it can be concluded that the incentive in the form of challenges and opportunities to improve one's career can increase work ethics.Abstrak. Penyuluh Agama Kristen menghadapi tantangan besar dalam menjalankan tugas-tugasnya sehingga membutuhkan etos kerja yang tinggi agar dapat memaksimalkan kinerja mereka. Tujuan riset ini adalah untuk menganalisis berbagai faktor yang mempengaruhi kinerja para Penyuluh Agama Kristen. Melalui riset kuantitatif dilakukan analisis faktor yang memberi pengaruh signifikan terhadap etos kerja para Penyuluh Agama Kristen di Kementerian Agama Kabupaten Toba. Hasil penelitian menunjukkan bahwa di antara faktor sistem pengembangan karir, faktor gaji, faktor lingkungan kerja, faktor sosial masyarakat, faktor kompetensi dan faktor apresiasi, faktor sistem pengembangan karir paling dominan dapat meningkatkan etos kerja para Penyuluh Agama Kristen. Dengan demikian dapat disimpulkan bahwa adanya insentif berupa tantangan dan kesempatan untuk meningkatkan karir dapat meningkatkan etos kerja.